SECULARISM AND ISLAMOPHOBIA: HISTORICAL RECONSTRUCTION OF THE FALL OF CHINA'S IDEOLOGY AND ECONOMY - Ku Ares Tawandorloh; Ardareena Chema; Kamaludin Kamaludin (Universitas Pendidikan Indonesia, 2021)
Islamophobia is an issue raised by Islamic antagonist groups to portray Islam as a radical, anarchist and primitive religion. Secularism is a thought product with the concept of separating religion and the world, which is being forced to become an ideology that is accepted internationally. China, as an influential economic country in the world, provides penetration with its economic strength so that ideas that are contrary to Islamic principles dominate global ideologies. No matter how great an ideology is, it turns out to have a fragility, this is what the Chinese State has forgotten. Success in the economic field has in fact caused problems in various sectors. This article presents the historical facts of how the fall of China's power was due to over-imposing an ideology that contradicts the holy Islamic shari'ah. The research method used in this research is descriptive analysis method. The research data were collected from various sources, then analyzed using the literature review technique. The results showed that the influence of cultural values, selfishness, high nationalism culture accompanied by the political heat of the country, became a barrier for Chinese people to accept the values of the spirit of faith contained in Islamic teachings.